2015
DOI: 10.3109/09513590.2015.1106471
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal acetate for uterine fibroids: a systematic review and meta-analysis

Abstract: Ulipristal acetate (UA), a selective progesterone modulator, has been approved for short-term therapy for symptomatic fibroids. We decided to undertake a systematic review of the best available evidence and draw a more definitive conclusion regarding the efficacy of UA for the management of uterine fibroids. The outcomes included symptomatic relief, quality of life-related parameters, reduction in fibroid size, side effects and recurrence rate. We included four randomised controlled trials which consisted of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
2
22
0
2
Order By: Relevance
“…Our findings are consistent with and extend those presented in a previous review . Their meta‐analysis was based on four studies and showed that UPA was associated with improved quality of life and reduced fibroid size compared with placebo.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with and extend those presented in a previous review . Their meta‐analysis was based on four studies and showed that UPA was associated with improved quality of life and reduced fibroid size compared with placebo.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that Short-term use of Ulipristal acetate is effective and safe method of treating uterine fibroids. 20 All these findings were similar to findings of our study which showed that administration of Ulipristal acetate was associated with decreased blood loss and fibroid size consequently causing improved quality of life.…”
Section: Discussionsupporting
confidence: 82%
“…In PEARL IV, 451 patients were treated for four recurrent 12‐week courses, with a daily dose of 5 or 10 mg UPA resulting in similar bleeding control, fibroid volume reduction and reassuring safety results . A systematic review and meta‐analysis of UPA as short‐term therapy for symptomatic fibroids included the RCTs mentioned earlier. Although they observed an improved quality of life and the reduction of fibroid size using UPA, they were unable to quantify a summarised improvement for most outcomes with the exception of amenorrhea, due to the heterogeneity of available data …”
Section: History and Mechanisms Of Actionmentioning
confidence: 99%
“…A systematic review and meta‐analysis of UPA as short‐term therapy for symptomatic fibroids included the RCTs mentioned earlier. Although they observed an improved quality of life and the reduction of fibroid size using UPA, they were unable to quantify a summarised improvement for most outcomes with the exception of amenorrhea, due to the heterogeneity of available data …”
Section: History and Mechanisms Of Actionmentioning
confidence: 99%